From world war to cold war : churchill, roosevelt, and the international history of the 1940s - Reynolds, David (Oxford : Oxford University Press, 2010)
The 1940s was probably the most dramatic and decisive decade of the twentieth century. In this volume, the leading international historian David Reynolds has brought together a collection of incisive essays, five of them previously unpublished, to explore some of the major themes, events, and personalities of this pivotal decade.
Introduction ; I: WORLD WAR ; 1. The Origins of 'The Second World War': Historical Discourse and International Politics ; 2. 1940: Fulcrum of the Twentieth Century? ; 3. Churchill, Roosevelt, and the Wartime Anglo-American Alliance ; II: CHURCHILL ; 4. Churchill and the British 'Decision' to Fight on in 1940: Right Policy, Wrong Reasons ; 5. Churchill the Appeaser? Between Hitler, Roosevelt, and Stalin 1940-1944 ; 6. Churchill and Allied Grand Strategy in Europe 1944-1945 ; III: ROOSEVELT ; 7. The President and the King: The Diplomacy of the British Royal Visit of 1939 ; 8. The President and the British Left: The Appointment of John Winant as US Ambassador in 1941 ; 9. The Wheelchair President and his Special Relationships ; IV: 'MIXED UP TOGETHER' ; 10. Whitehall, Washington, and the Promotion of American Studies in Britain 1941-1943 ; 11. Churchill's Government and the Black GIs 1942-1943 ; 12. GIs and Tommies: The Army 'Inter-Attachment Programme of 1943-1944 ; V: COLD WAR ; 13. Churchill, Roosevelt, and the Stalin Enigma ; 14. Churchill, Stalin, and the 'Iron Curtain' ; 15. The 'Big Three' and the Division of Europe 1945-1948 ; VI: PERSPECTIVES ; 16. Power and Superpower: The Impact of the Second World War on America's International Role ; 17. A Special Relationship? America, Britain, and the International Order since World War Two ; 18. Culture, Discourse, and Policy: Reflections on the New International History ; Index
ENH
Keywords: World War, 1939-1945 -- Diplomatic history; World politics -- 1945-1955.; English literature; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; United States -- Foreign relations -- 1933-1945.; Great Britain -- Foreign relations -- 1945-1964.